2013
DOI: 10.1007/s12291-012-0293-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disorders in Patients of Type 2 Diabetes Mellitus

Abstract: The study was planned to assess the prevalence of thyroid disorders in type 2 diabetes in North Indian population and to correlate the serum insulin and glycosylated haemoglobin levels with thyroid hormones. It is a case control study. One hundred and twenty patients of type 2 diabetes were included in the study along with 117 adults of the same age group and normal glucose levels as controls. All blood samples were taken from subjects who fasted for at least 12 h before the blood collection. Glycosylated hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 19 publications
6
26
0
1
Order By: Relevance
“…The average PPBS in this population is 212 mg/dl with 95% of them in between 196-228 mg/dl which is almost similar to previous study. Distribution of HbA1C shows 95% (2 SD) of population are within 8.02-8.96%, well above the good control (<7%) consistent with Vibha Uppal et al 25 Distribution of FT4 level is normal in maximum no of patients whereas that of FT3 is towards lower range of normal value. But TSH level is significantly abnormal reflecting underlying thyroid abnormality in maximum population, which in accordance with Celani et al 26 In our study we found a low T3 state with significantly increased fasting blood glucose, HbA1C.…”
Section: Discussionsupporting
confidence: 85%
“…The average PPBS in this population is 212 mg/dl with 95% of them in between 196-228 mg/dl which is almost similar to previous study. Distribution of HbA1C shows 95% (2 SD) of population are within 8.02-8.96%, well above the good control (<7%) consistent with Vibha Uppal et al 25 Distribution of FT4 level is normal in maximum no of patients whereas that of FT3 is towards lower range of normal value. But TSH level is significantly abnormal reflecting underlying thyroid abnormality in maximum population, which in accordance with Celani et al 26 In our study we found a low T3 state with significantly increased fasting blood glucose, HbA1C.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, we found that the trend of hypothyroidism increased significantly with increasing fasting blood glucose (Figure-1). The associations between hypothyroidism and diabetes have been reported in other studies and in other forms of diabetes [6,7,[18][19][20][21][22]. A study found a higher TSH level in patients with metabolic syndrome suggesting that hypothyroidism may be a risk factor for it [23].…”
Section: Discussionmentioning
confidence: 80%
“…11,12 The logical explanation of the lower prevalence is due to iodine replete status of the middle east countries and difference in thyroid function assay methods. [13][14][15][16][17] The explanation of increased prevalence reported in most of the Indian studies may be due to our country is having mixed population with iodine deficient and iodine replete status. There may be a genetic or environmental (goitrogens) angle of explanation too.…”
Section: Discussionmentioning
confidence: 99%